PENGEMBANGAN MEDIA BELAJAR ENGLISH FOR CHILDREN (EFC) DENGAN MEMANFAATKAN LIMBAH INDUSTRI GARMEN - Suharto, G; Supriyanti, Nury; Jamilah, Jamilah; Purnawan, Ari (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
This   workshop    is  aimed   at  providing   knowledge    and   skills   in':.~5g· ning classroom  activities,  creating  and developing  learning  media  from~~ent       waste,   and   its  implementation    in  the  teaching   of  English   for~;,'  ren  by  kindergarten    teachers   in  the  Subdistrict   of  Kalasan,   Sleman. egency, Yogyakarta   Special  Territory.The   presentation    method   includes   lecturing,   demonstrating,     and;::-a tising. Lecturing  was employed  in presenting  the theoretical  and  literary.e 'iews on teaching  children,  and in seeking   for new alternatives  to support:.~  teachers'  creativity  in developing  the learning  media. Demonstrating   was conducted  in designing   classroom  activities  and lesson  units,  making  media zppropriate  for  the  classroom   activities,and   managing  the  teaching-leming.  ocess with the focus on the optimal  use of the media. The teaching  practice.: at was then  carried  out  by the  participants   included  making  lesson  units.or the  classroom   activities,   creating  learning  media,  and  carrying   out  the.eaching-learning   process  in the form of micro teaching.This workshop  resulted  in the improvement  of knowledge  about  new ends in English  teaching,  the improvement  in the skills of designing  lesson units  and  creating   learning   media,   the  improvement    in  the  teaching   of English  using   the  media,   and  the  eleven   sets  of  media   model   for  theteaching of English  using  garment  waste of various  kinds.Key words: English/or   children, media